TOURISM POLICY OF UZBEKISTAN IN 1945- 1991 - Ernazarov Faizullo Narzullaevich (Western European Studies, 2024)
It is known from the world experience that the socio-political, economic and cultural development of countries depends in many ways on the attitude towards tourism. Some countries in the world, based on their capabilities, ensure the financial stability of the country at the expense of the income that comes through the development of tourism. Tourism, in its essence, also plays a significant role in the development of inter-civilizational harmony. We can determine the future priorities of this industry through our in-depth study of the history of tourism. This article was prepared taking into account these aspects, historical facts about the main characteristics, problems, shortcomings and achievements of tourism policy in Uzbekistan from 1945 to 1991 were studied and analyzed. Also, while reading the article, a clear idea of the tourism policy of Uzbekistan from 1945 to 1991 will appear
Keywords: Tourism; national culture; USSR; Intourist